HUBUNGAN ORIENTASI NILAI BUDAYA DAN PENDIDIKAN YANG DIPEROLEH DENGAN JIWA WIRAUSAHA BAGI PENDUDUK DESA TERTINGGAL DI DAERAH ISTIMEWA YOGYAKARTA - Sigit Dwi Kusrahmadi (LPPM UNY, 2005)
Abstract The purpose of this study is to know the relationship between cultural value orientation and the spirit of entrepreneurship for the lagged villagers, between the level of education and the spirit of entrepreneurship, between the cultural value orientation and the education resulted from the entrepreneurship, as well as the contribution of cultural value orientation and education resulted from the spirit of entrepreneurship in the lagged villages in Yogyakarta Special Territory. The population of study is the lagged villagers in Yogyakarta Special Territory (YST). The sampling technique is Quota Area Proportional Random Samplling in which the subject have been determined and the number of lagged villagers are 12 villages. The method of compile data is the polling method for cultural value orientation, education, and the spirit of entrepreneurship is taken from Wisnu Giono (2004). Based on the results of the study, it can be concluded that (1) there is a significant and positive relationship between cultural value orientation and the spirit of entrepreneurship for the lagged villagers in YST (r xly=0.937 r table 5%=0.138). (2) there is a significant and positive relationship between education and the spirit of entrepreneurship for the lagged villagers in YST (r x2y=0.963 r table 5%=0.138). (3) there is a significant and positive relationship between cultural value orientation and education all together with the spirit of entrepreneurship for the lagged villagers in YST (F reg=1,257.78 Ftable 5%=19.49). (4) there is a relative and effective contribution of cultural value orientation and education to the spirit of entrepreneurship for the lagged villagers in YST (Predictor XI= cultural value orientation has a relative contribution (RC) of 0.005% and Predictor X2= education found has a relative contribution (RC) of 99.995% to the spirit of entrepreneurship and totally has an effective contribution (EC) of 91.425% to the spirit of entrepreneurship). Keywords: cultural value orientation